Developing Thai EFL Learners’ Email Literacy in Business Communication Course at Tertiary Level, Thailand - Wei, Xiaoxia (Scholar: Human Sciences, 2017)
The study followed a pre-test-instruction-post-test design to examine the effectiveness of teaching business emails to a group of 111 Thai students who enrolled a Business Communication course conducted in a business program for undergraduates, Thailand. The research aimed to find out 1) the development of students’ business email writing after the explicit instructions and 2) in what aspect(s) students’ business email writing will improve. A Total of 222 email scripts collected before and after the 12-week explicit instructions was analyzed quantitatively by paired t-tests. The findings showed that the students had significant gains in each evaluation aspect of the email writing task in the post-test after the explicit instructions. The students improved greatly in terms of the Content, Organization, as well as Framing moves, as demonstrated by the greater use of concrete subject headings, correct greeting and closing constructions, complete self-identifications on the post-test than on the pre-test. On the other hand, students made only modest progress in terms of Business Writing Style, more specifically, students were more aware of using more polite and professional business writing tones in the task. However, there was little progress in terms of students’ Language Proficiency in general according to the paired score difference in both tests. These findings are discussed with implications for classroom practices and future research.